Optimasi Parameter Pembuatan Genteng Keramik Pres Terhadap Respon Kuat Lentur dan Kuat Serap Air - Suhartoyo, Suhartoyo; Kristiawan, Y Yulianto (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Roof tiles are roof coverings that function to protect the lower part from the heat of the sun and rain. Roof tiles are usually made from earth, either pressed or printed and from cement. Good quality roof tiles do not leak easily, are neat when arranged, have a uniform size and shape, and do not break easily or become mossy. This research aims to determine the quality of roof tiles in terms of the parameters of strength against water seepage and strength to withstand bending loads. The results of calculating the signal-to-noise ratio for the strength to withstand the bending load of roof tiles from several variations of tests that have been carried out show that the A1 factor is 49.2469. To minimize the value of water absorption strength (%), a combination of level factors is needed, including a roller diameter (A) of 250 mm, engine rpm (B) of 1000 rpm, gap between rollers (C) of 3 mm, and material mixture ratio ( D) the mixture of ingredients used is kaolin: water: clay: sand is 0.35: 0:25. 1: 0.5. The optimal combination of factor levels, for both responses, the strength to withstand bending loads and the strength to resist water seepage, have the same maximum value (A3 B1 C3 D2), so there is no need to carry out a confirmation test. From the calculation of the signal-to-noise ratio for the strength to resist water seepage, it can be seen that the coefficient that responds is coefficient A1 is -25.4842. Keywords: Ceramic tiles, Factors, Flexural strength, Level, Water absorption